Community paramedic‐delivered care transitions intervention reduces emergency department revisits among cognitively impaired patients. (31st December 2021) - Shah, Manish N; Green, Rebecca K; Jacobsohn, Gwen C; Jones, Courtney MC; Caprio, Thomas V; Cochran, Amy L; Cushman, Jeremy T; DuGoff, Eva; Lohmeier, Michael; Kind, Amy J
Abstract: Background: Up to half of community‐dwelling older adults with impaired cognition who are discharged home from the emergency department (ED) return for further care within 30 days. We examined the effects of delivering the Care Transitions Intervention (CTI) to older adult patients with impaired cognition discharged home from the ED, hypothesizing that the CTI would decrease ED revisits in the following 30 days. Method: We conducted a pre‐planned sub‐analysis of community‐dwelling older adults (age≥60 years) with impaired cognition participating in a single‐blind, randomized controlled trial testing the effectiveness of the CTI adapted for use following ED discharge. The parent study recruited ED patients from three university‐affiliated hospitals from 2016–2019. Subjects eligible for this analysis had to: 1) have a primary care provider within these health systems; 2) be discharged to a community residence; 3) not receive care management or hospice services; and 4) be cognitively impaired in the ED, as determined by a score>10 on the Blessed Orientation Memory Concentration Test. Intervention group subjects received a home visit from a trained paramedic coach within 72 hours of discharge, and up to three follow‐up phone calls during the following month. Our primary outcome was occurrence of any ED revisit within 30 days of discharge. Secondary outcomes included any ED revisit within 14 days and outpatient clinic follow‐up. We evaluated intervention effects using multivariate logistic regression. Result: Of our sub‐sample (N=81, 36 control, 45 treatment), 57% were female and the mean age was 78 years. Bivariate comparison of primary and secondary outcomes found no significant differences. Multivariate analysis, adjusted for the presence of moderate to severe depression and inadequate health literacy, found that the CTI significantly reduced the odds of a repeat ED visit within 30 days (OR 0.25, 95%CI 0.07‐0.90) but not 14 days (OR 1.01, 95%CI 0.26‐3.93). Multivariate analysis of outpatient follow‐up found no significant effects. Conclusion: Community‐dwelling older adults with cognitive impairment receiving the CTI following ED discharge experienced fewer ED revisits within 30 days compared to usual care. Further studies must confirm and expand upon this finding, identifying features with greatest benefit to patients and caregivers.